Ocenočnyj suffiks - k - v russkom jazyke - Kalasniemi, Mirja (1992)
Although evaluation is an essential part of the linguistic activity of human beings, it has been relatively little researched. This study endeavours to analyse how evaluation is carried out in Russian by means of evaluative nominal suffixes, in particular the suffix -#k-, which represents the most productive type. In previous research, evaluative suffixes have been dealt with as emotive suffixes whereas, in the present study, a new angle is introduced which focuses on their evaluative character. The concept of scalarity (e.g. good vs. bad), which has been derived from axiology, sheds new light on the special character of evaluative suffixes. The diminutiveness of Russian evaluative suffixes is seen as an indivisible whole containing a quantitative as well as a qualitative component by means of which evaluation takes place on the axle "approval vs. disapproval". An axiology-based approach will also shed new light on the interpretation of suffixes in the linguistic context provided by the modern Russian short story. The systematisation and classification of the interpretations is based on the distinction between (1) sensory, (2) sublimated and (3) rational values. The first group is made up of so-called psychological values which are further divided into intellectual, e.g. irony, or significanse vs. insignificanse (of a person or thing) and emotional values, e.g. sympathy vs. antipathy or satisfaction vs. dissatisfaction (with something). The second group consists of ethical, e.g. respect vs. disrespect (for a person) and aesthetical values, e.g. beauty vs ugliness (of nature in particular). For the first time in the research tradition, rational values are introduced, e.g. coziness vs. uncoziness (e.g. of a room), ability vs. inability (e.g. of a person). The setting up of the evaluative scales mentioned above was only possible on the basis of illocutionary acts; therefore a separate analysis is made of each of the four illocutionary types: representatives, expressives, comissives and directives. The research approach could be briefly characterized - analogously to "word-formational semantics” - as "word-formational pragmatics".